Monitoring of Circulating Tumor Cells by a Combination of Immunomagnetic Enrichment and RT-PCR in Colorectal Cancer Patients Undergoing Surgery - Vojtěchová, Gabriela; Mináriková, Lucie; Belsanova, Barbora; Mináriková, Petra; Levý, Miroslav; Lipská, Ludmila; Suchánek, Štěpán; Zavoral, Miroslav; Minárik, Marek (Advances in clinical and experimental medicine, 2016)
BACKGROUND: The presence of circulating tumor cells (CTC) has been reported in patients with advanced colorectal cancer. Monitoring CTC (also known as a liquid-biopsy) has recently become the center of interest for low-invasive monitoring of cancer progression and predictive biomarkers testing. Along with high-cost technology and a complex methodology, a straightforward method based on magnetic beads enrichment followed by RT-PCR is set to allow for routine CTC analysis in colorectal cancer patients. OBJECTIVES: The main purpose of this study was to evaluate the possibility of CTC detection in routine monitoring of patients starting before and continuing after surgery. MATERIAL AND METHODS: The investigated group consisted of 30 patients mainly in advanced stages of colorectal cancer. In all patients, CTC detection was performed prior to surgery, in a subset of 14 patients additional sampling was done during and after surgery. In all cases, peripheral blood was processed using AdnaTest ColonCancer kit, which relies on enriching CTCs using EpCAM-functionalized magnetic beads and subsequently identifying tumorspecific CEA, EGFR and GA733-2 mRNA transcripts. RESULTS: Out of all the tested samples, CTC were found in one patient suffering from advanced disease with lung and liver metastases. There, however, the positive finding was confirmed in 3 consecutive samples acquired before, during and shortly after palliative R2 resection. CONCLUSIONS: The presence of CTC may be used to observe post-operative disease development. Due to the overall low CTC detection, further technology development may be necessary before its universal applicability to manage colorectal cancer patients.
Keywords: Colorectal Neoplasms; kolorektální nádory; lidé; nádorové cirkulující buňky; senioři; mužské pohlaví; Female; Immunomagnetic Separation; Male; kolorektální chirurgie; imunomagnetická separace; Aged; Reverse Transcriptase Polymerase Chain Reaction; Neoplastic Cells, Circulating; polymerázová řetězová reakce s reverzní transkripcí; Colorectal Surgery; ženské pohlaví; Humans